Competitiveness—the engine that boosts economic growth and revives the economy - Vîrjan, D.; Manole, A. M.; Stanef-Puică, M. R.; Chenic, A. S.; Papuc, C. M.; Huru, D.; Bănacu, C. S. (Frontiers in Environmental Science, 2023)
Competitiveness is a notion encountered in all aspects of human life, both at the micro level, in personal, social, and professional life, and at the macro level, linked to organizational and national competitiveness. In this paper we address competitiveness in Romania in the current context, before and after the COVID 19 pandemic, highlighting its role in reviving the economy. In order to have a clear picture of the degree of competitiveness in Romania, we presented a series of statistical data for the most relevant macroeconomic indicators for our study: global competitiveness index, minimum wage, labor productivity, evolution of real labor productivity per employed person, economic growth rate, unemployment rate, inflation rate, European innovation index, gross domestic expenditure on research and development, export of goods and services as a share of GDP, etc. The methodology used involves the use of quantitative techniques, performing an econometric analysis, and correlating how the most important macroeconomic indicators can influence the degree of competitiveness at both national and international level. For the post-pandemic timeframe, the analysis switches focus, just as the economic reality did, looking at energy costs and energy use as determinants of competitiveness. Since notions like circular economy and sustainable development correlate being energy-efficient with being competitive, however, at the same time, the high cost of investments necessary for individual businesses and countries to switch from polluting energies to clean energies impedes their ability to compete with entities that don’t make that same switch, it becomes apparent that the energy market impacts competitiveness metrics. Competitiveness promotes valuable contributors and underpins performance at group and company level, and the effects from the micro level will propagate, with an emission effect, to the entire national economy with obvious implications at international level, through real growth in macroeconomic indicators, increased labor productivity, increased economic performance, in raising living standards and economic and social well-being (life expectancy index, human development index, poverty rate), in education (skills, knowledge, abilities, managerial and marketing skills, corporate culture), in competitive potential (innovation, R&D, promotion) and in raising the Global Competitiveness Index by focusing on factors of production, efficiency and innovation, etc.